2022
DOI: 10.1002/tcr.202100323
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress, Challenges, and Opportunities of Membrane Distillation for Heavy Metals Removal

Abstract: Water is essential for the presence of life on this earth. However, water contamination due to the presence of heavy/toxic metals is one of the serious environmental issues for living beings. Several methods have been devoted to separating or removing those heavy metals from wastewater. Among them, membrane distillation (MD) has become one of the most attractive approaches due to its higher rejection rate than processes driven by pressure, lower energy consumption than traditional distillation processes. MD ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…It may occur to readers that some of the spice metals have from time to time been labeled "heavy metals" as a consequence of their possible health effects (e.g., Aposhian (1983) [77], Ordog (2006) [78], Aijaz et al, (2022) [79]). The use of the term "heavy metals" has, however, long been shown to be arbitrary and imprecise [80].…”
Section: Discussionmentioning
confidence: 99%
“…It may occur to readers that some of the spice metals have from time to time been labeled "heavy metals" as a consequence of their possible health effects (e.g., Aposhian (1983) [77], Ordog (2006) [78], Aijaz et al, (2022) [79]). The use of the term "heavy metals" has, however, long been shown to be arbitrary and imprecise [80].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in all cases, the efficiency of the above membrane processes drops rapidly as soon as the feeding conditions depart from optimized pH and concentrations. An extensive treatise of all the membrane processes for metal ions removal is far beyond the scope of this review and further reading of the relevant publications on each subject as reported in Table 3 (entries 1-10) and recent reviews [101][102][103] are recommended. Among the various membrane processes for heavy metal removal, adsorptive membrane technology so-called also membrane adsorbers (Table 3, entry 11) has gained great attention [104][105][106][107] thanks to lower pressure demands and lower energy of membrane operation without compromising the adsorption selectivity.…”
Section: This Review and References Hereinmentioning
confidence: 99%
“…Membrane distillation, an emerging technology known for its high separation efficiency and capability of extracting freshwater and useful resources from wastewater, , has attracted increasing interest during the past decade. Zuo et al explored the feasibility of commercial hydrophobic polyethylene (PE) membranes used for membrane distillation of highly saline solutions (3.5% NaCl solution) . Their results revealed that the commercial hydrophobic PE membranes possessed promising desalination efficiency (99.9%) in treating NaCl solutions by membrane distillation with a permeation flux of 123.0 L·m –2 ·h –1 at a transmembrane temperature difference of 63 °C.…”
Section: Introductionmentioning
confidence: 99%